Aortic Periannular Abscess Missed by Transthoracic Echocardiography: A Case Report - Wenjuan He; Yudong Peng; Yan Yi; Han Hu; Jinzhi Lu; Keming Chen; Qingsong Zeng (Clinical Case Reports)
ABSTRACT An aortic periannular abscess (PA) is a critical consequence of infective endocarditis (IE). In our case report, the patient's clinical symptoms were only fever, cough, and shortness of breath. He was then diagnosed with aortic PA, which was overlooked in the initial TTE assessment but later identified through transesophageal echocardiography (TEE). The patient underwent surgery immediately and recovered well. This case underscores the importance of TEE in revealing small, yet critical, intracardiac lesions that may be missed by TTE.